Tinjauan Yuridis Tindak Pidana Perbankan Yang Berkaitan Dengan Usaha Bank (Studi Kasus Putusan Pengadilan Nomor 2644/Pid.b/2021/PN Mdn) - Asry Silvia Wulandari (Cakrawala Repositori IMWI, 2023)
This juridical review aims to determine the factors that cause banking crimes at banks in tackling banking crimes against banking crimes at banks. This juridical review uses a normative approach, namely by focusing on the study of regulations relating to banking crimes related to bank business. In addition, this study was carried out through juridical activities. This research was conducted by examining banking crimes related to bank business. The results of this juridical review show that the factors that lead to banking crimes at banks are economic factors, opportunity factors, and technological development factors.